Targeting cyclin D1 as a therapeutic approach for papillary thyroid carcinoma - Cai, Wei; Shu, Lin-Zhen; Liu, Ding-Jie; Zhou, Lv; Wang, Meng-Meng; Deng, Huan (Frontiers in Oncology, 2023)
Cyclin D1 functions as a mitogenic sensor that specifically binds to CDK4/6, thereby integrating external mitogenic inputs and cell cycle progression. Cyclin D1 interacts with transcription factors and regulates various important cellular processes, including differentiation, proliferation, apoptosis, and DNA repair. Therefore, its dysregulation contributes to carcinogenesis. Cyclin D1 is highly expressed in papillary thyroid carcinoma (PTC). However, the particular cellular mechanisms through which abnormal cyclin D1 expression causes PTC are poorly understood. Unveiling the regulatory mechanisms of cyclin D1 and its function in PTC may help determine clinically effective strategies, and open up better opportunities for further research, leading to the development of novel PTC regimens that are clinically effective. This review explores the mechanisms underlying cyclin D1 overexpression in PTC. Furthermore, we discuss the role of cyclin D1 in PTC tumorigenesis via its interactions with other regulatory elements. Finally, recent progress in the development of therapeutic options targeting cyclin D1 in PTC is examined and summarized.